Arkitektens roll och arbetssätt vid industriellt byggande med trävolymmoduler : Hur dessa förändras jämfört med traditionellt byggande - Lundin, Sandra (2013)
This thesis is about how the architect’s role and approach change when building industrially with wood volume modules rather than traditionally. Since industrial building is a very wide concept, the focus of this thesis has been primarily on industrially built apartments. A literature review, five comprehensive interviews with architects who have worked with volume modules of wood and a case study of the project Brf Trädgården has formed the basis for the analysis and conclusions. The literature review showed that industrial construction is stuck with a bad view since Miljonprogrammet. Today, the conditions are quite different, but people are still afraid that industrial constructed projects are synonymous with monotonous and inane. There are different types of building systems where the variation is very wide and no building needs to be the same. It was also shown that the role of the architect and the way of working has changed many times throughout history. Once upon a time the profession architect and engineer meant the same thing and the two professions had similar skills but worked in different types of projects. Today, it is more likely that you are working on the same project but with different areas of knowledge. During the interviews, it became obvious that the most important parameter for an industrial built project to be good is the attitude from all involved. They must work as a team and have the same vision and goal with the project. The case study provided deeper knowledge of how an industrial project process goes and observations were made continuously for five months. The conclusion is that the architect’s role and work do not have to change just because the project is going to be built industrial. However, the analysis showed that it is easier to achieve a good result if the architect follows the whole process and is involved in developing the industrial system. It also showed that the architect’s role may evolve to become more of a central figure and information coordinator. Today, the role of ...